BAHASA PRIA DAN WANITA: KAJIAN SOSIOLINGUISTIS PADA MAHASISWA UNIVERSITAS PGRI PALEMBANG - Sholikhah, Hani Atus (Lentera: Jurnal Ilmiah Kependidikan, 2015)
The issues discussed in this research is the analysis of verbalistis by gender, with sample language differences among male and female students at the University PGRI Palembang. Based on the data, the results are as follows: (1) The use of sound and intonation (P: 50% and W: 50%); (2) the intensity of talk (P 30% and W: 70%); (3) skill in verbalistis (P 30% and W: 70%); (4) observation (P: 50% and W: 50%); (5) competitive and cooperative (P 50% and W: 70%); (6) Miscommunication (P: 50% and W: 50%). From the data, it was concluded the following. (1) The issue of language and communication is more important for women than men because women more often speak of the men. (2) The purpose of men in the use of language tends about getting something, whereas women tend to be about making relationships with others. More men are talking about data and facts, while more women are talking about people, feelings, and relationships between people. (3) Women are more verbally skilled compared to men. (4) The difference often leads to "miscommunication" between women and men. (5) The way men use language to be competitive in obtaining and maintaining the status. How to use the language of women are cooperative, reflecting their preference for equality and harmony.